The Validation study of Adjuvant Online using Iranian breast cancer data - Ghanbari Motlagh, Ali; Mojir Sheibani, Khosro; Novin, Kambiz; Tabatabaeefar, Morteza; Azadeh, Payam; Mafi, Ahmad R; Moghadam, Shiva; Hoseini Kamal, Farnaz (Reports of Radiotherapy and Oncology, 2023)
Background: Adjuvant Online! (AOL) is used extensively by oncologists in Iran to treat patients with breast cancer; however, it has never been validated for use in Iran, and its predictions might not be applicable to Iranian patients. The aim of this study was to evaluate the usefulness of this program in predicting the outcomes of Iranian patients with breast cancer. Patients and methods: 368 patients who were treated between 1997 and 2010 at Jorjani Cancer Center entered the study. Data for each patient, including tumor size, number of positive nodes, tumor grade, ER status, and adjuvant systemic therapy, were entered into the AOL program (version 8.0), and the calculated disease free survival (DFS) was compared with the observed one. Analyses were performed using Cox regression modeling and SPSS 17.0 software, and P values < 0.05 were considered significant. Results: Observed disease free survival (DFS)in our study was 72 months, while the calculated DFS by AOL was 68 months. In all subgroups of AOL, calculated DFS was less than observed DFS except for patients receiving Tamoxifen + Aromatase Inhibitors + Ovarian Ablation hormone therapy, for whom the calculated DFS was 2 percent more than the observed one. Conclusions: AOL underestimated overall survival and disease free survival rates in Iranian patients with breast cancer, which in our opinion was mainly due to the shorter period of follow-up in our study. Although AOL is widely used by Iranian oncologists, we believe that developing an Iranian version of a prediction tool would better predict the prognosis of our patients.